2021
DOI: 10.1002/imhj.21954
|View full text |Cite
|
Sign up to set email alerts
|

Adapting psychophysiological data collection for COVID‐19: The “Virtual Assessment” model

Abstract: The COVID‐19 pandemic has significantly disrupted research activities globally. Researchers need safe and creative procedures to resume data collection, particularly for projects evaluating infant mental health interventions. Remote research is uniquely challenging for psychophysiological data collection, which typically requires close contact between researchers and participants as well as technical equipment frequently located in laboratory settings. In accordance with public health guidance, we adapted proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Patterns of autonomic reactivity were similar across home and lab settings (Tabachnick et al, 2022), and community data suggest that intervention fidelity and effects on parenting were maintained in the transition to telehealth (Roben et al, 2022;Schein et al, 2022). Further information regarding RCT enrollment and attrition is provided in Supplement 1.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Patterns of autonomic reactivity were similar across home and lab settings (Tabachnick et al, 2022), and community data suggest that intervention fidelity and effects on parenting were maintained in the transition to telehealth (Roben et al, 2022;Schein et al, 2022). Further information regarding RCT enrollment and attrition is provided in Supplement 1.…”
Section: Methodsmentioning
confidence: 93%
“…Data collection continued with remote assessment only (e.g., interviews by Zoom) until mid‐July 2020, when in‐person data collection resumed on a limited basis, with some families electing remote‐only or home assessments with virtual researcher support. Patterns of autonomic reactivity were similar across home and lab settings (Tabachnick et al., 2022), and community data suggest that intervention fidelity and effects on parenting were maintained in the transition to telehealth (Roben et al., 2022; Schein et al., 2022). Further information regarding RCT enrollment and attrition is provided in Supplement 1.…”
Section: Methodsmentioning
confidence: 99%
“…Our study sample is socioeconomically diverse, and thus far we have found that mothers across the socioeconomic spectrum have been able to participate in the remote assessments. Remote assessments enable participants with fewer resources, who may have felt compelled to complete in-person assessments for compensation despite concerns about viral exposure, to receive the benefits of participation safely and autonomously, further reducing potential bias in the sample . In some geographic regions, it may be necessary to provide participants with mobile hotspots to ensure high-quality data collection.…”
Section: The Covid-19 Pandemic In Context: Prior Research and Recomme...mentioning
confidence: 93%
“…Three primary goals should be considered when developing such protocols: (1) prioritizing safety of the participants and researchers, (2) optimizing data quality through pilot assessments and clear instructions for participants, and (3) minimizing participant burden by providing organized and simplified study materials . Following these principles, our ongoing COVID-19 Mother Baby Outcomes (COMBO) initiative administers a modified version of the Developmental Assessment of Young Child, Second Edition (DAYC-2), an observer-based assessment of infant neurodevelopment, through a Zoom session at 6 to 12 months of age.…”
Section: The Covid-19 Pandemic In Context: Prior Research and Recomme...mentioning
confidence: 99%
“…Potential solutions to these barriers include remote assessments that can be conducted at a time convenient to the family. For example, in response to the pandemic, our lab (Gao et al, 2022) and others (Tabachnick et al, 2022) have found ways to support families by collecting physiological data in the home.…”
Section: Gaps In Emotion Dysregulation Researchmentioning
confidence: 99%